2012
DOI: 10.1186/ar3922
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling and functional analysis of angiogenic markers in murine collagen-induced arthritis

Abstract: IntroductionDysregulated angiogenesis is implicated in the pathogenesis of rheumatoid arthritis (RA). To provide a more profound understanding of arthritis-associated angiogenesis, we evaluated the expression of angiogenesis-modulating genes at onset, peak and declining phases of collagen-induced arthritis (CIA), a well-established mouse model for RA.MethodsCIA was induced in DBA/1 mice with type II collagen. Functional capillary density in synovial tissue of knee joints was determined by intravital fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…We propose the following explanations for why and how DAAP is more effective than VEGF-Trap or Tie2-Fc. First, arthritic synovium has strong expression and activation levels of VEGF-A, PIGF, Ang-1 and Ang-2, and their expression patterns were different according to disease stages of RA in our data and other reports [15,24-27]. Our previous study showed that DAAP is able to bind to VEGF-A, PIGF, Ang-1, Ang-2 and Ang-3/Ang-4.…”
Section: Discussionsupporting
confidence: 60%
“…We propose the following explanations for why and how DAAP is more effective than VEGF-Trap or Tie2-Fc. First, arthritic synovium has strong expression and activation levels of VEGF-A, PIGF, Ang-1 and Ang-2, and their expression patterns were different according to disease stages of RA in our data and other reports [15,24-27]. Our previous study showed that DAAP is able to bind to VEGF-A, PIGF, Ang-1, Ang-2 and Ang-3/Ang-4.…”
Section: Discussionsupporting
confidence: 60%
“…They also exhibit a set of pro‐regenerative features that make them attractive agents for both modulation of immune disorders and for regenerative therapy approaches. However, the microenvironments of inflamed synovium share some similarities with that of a cancer and wound, such as pronounced metabolic turnover and proliferating of blood vessels . Several studies have revealed that MSC are recruited to cancer and play a particularly important role in disease progression enhancing cancer cell survival and angiogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…The mice were examined for the onset and severity of arthritis every 2 weeks after pristane injection. For scoring of arthritis severity, we used a previously published scoring system with modification, as follows: score scale of 0–3, where 0 = normal, 1 = slight swelling or erythema of the wrist/ankle joint or footpad, 2 = moderate swelling and erythema of the wrist/ankle joint or footpad, and 3 = severe swelling and erythema of the paw. The scores for individual limbs were summed to obtain a total clinical arthritis severity score of 12 per animal.…”
Section: Methodsmentioning
confidence: 99%